(untitled) (Journal of Nepal Geological Society, 2018)
Landslides that are the major hazards, are concentrated along the river valley, road cut sections, cultivated lands and geologically adverse areas like fault zones, incompetent lithology, steep slopes and overhanging cliffs. Present study represents a small part of the Mahabharat Range within the Lesser Himalaya, where landslide inventory mapping was carried out in the Ramche-Jharlang area because it consists of numerous small to large landslides affecting ecology and society. The main objectives were to delineate both present and past landslides with their characters (geometry, geology, hydrogeology, slope geometry, triggering causes of landslides and their impacts) focusing on the present propagating trends in terms of its cause. The field investigation was carried out by field work in the landslide occurring areas, visual inspection, satellite image analysis, photographical analysis, interaction and interview with the locals and the affected groups. The study reveals nail scratching outlook in most of the hills. The slope failures were debris flow, debris slide, mud flow and deep-seated creeps. The Ramche landslide in the eastern part to the Jharlan-Chhyamthali in the western part, have been devastating and active now and then causing huge casualties. The utmost reasons for occurring small to large scale landslides are inherently weak geological setting along with some adverse geological structures in addition to the triggering factors like concentrated precipitation and earthquakes. Systematic landslide hazard mapping and mitigation measures based on the cause and consequences during the planning and construction stages of infrastructures are fundamental steps to reduce loss from landslide disaster in the region.